Derivation and verification of a similarity law for wind-tunnel free-flight tests of heavy-store separation. (September 2020) - Xue, Fei; Wang, Huaqiang; Jiang, Zenghui; Wang, Yuchao
Abstract: Test-method research was carried out to consider the separation of a heavy store, and a similarity law for unsteady wind-tunnel free-flight tests of air-launch rockets was derived. The derivation of this similarity law considers the particular characteristics of a heavy store and aerodynamic interference with the carrier and focuses on solving the following problems: the separation of a heavy store causes a real carrier to have an acceleration and a velocity that cannot be ignored; the carrier in a wind-tunnel test is vertically fixed; and a wind-tunnel test cannot meet the Froude number ( Fr ) similarity condition. According to the special characteristics of heavy-store separation, a similarity law for wind-tunnel free-flight tests of heavy-store separation is derived. Computational fluid dynamics simulations are used to verify the new similarity law. The results show that the new similarity law can simulate the separation trajectory more realistically than existing methods, and the linear and angular displacement errors are decreased by an order of magnitude. The experimental accuracy of the new similarity law is even higher than that of a separation trajectory satisfying Fr matching. It is demonstrated that the new similarity law can be used to carry out unsteady experimental research on the separation of a heavy store such as an air-launch rocket, and this new law provides strong support for establishing the safety boundaries of heavy-store separation. Highlights: The unsteady test method of wind tunnel test is innovated, and make up the heavy store research methods gap. In the new similarity law, the potential vertical acceleration and velocity of the carrier upward are considered. The test carrier cannot be moved and the Fr can't be simulated are considered in the paper. The new similarity law can simulate the separation trajectory more realistically on heavy store separation.